Women Caregivers from Community-Based Organizations: Between the Expectations for Professionalization and ‘Altruism’ - Zibecchi, Carla (2014)
The article proposes understanding women caregivers from community-based organizations, their strategies (for capitalization of experience and professionalization and training) and their expectations about their caregiving work in an empirical study based on in-depth interviews. The intention is to problematize some explanations that circulate regarding the participation of women in the community environment based on ‘altruism’. The results that are presented are based on a larger study that covers the modality under which community organizations provide caregiving services to broad sectors of the population.